Penilaian Efisiensi Pengelolaan Modal Kerja dan Kinerja Keuangan pada PT Duta Pertiwi Nusantara Tbk - Rina Rahmawati; Iwan Setiawan; Diharpi Herli Setyowati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to assess the efficiency of working capital management and the financial performance condition of PT. Duta Pertiwi Nusantara Tbk period 2014-2018. This type of research is descriptive of quantitative, using secondary data from the balance sheet and income statements. Data analysis techniques with source analysis and use of working capital and analysis ratio. The results of the research, analysis of the sources and the use of working capital, are not fully efficient because there are increases and decreases in working capital followed the fluctuations in the ratio profitablitas. Liquidity ratio fluctuates, the ratio is high above the industry general ratio standard, it is not fully efficient and the financial performance is overly liquid. Activity ratios and profitability ratios fluctuate and also tend to decline, the ratio is still low below the industry general ratio standard, so according to activity ratios and profitability ratios it is not efficicent and financial performance less good.